Relationship between sensory neuropathy and body imbalance among diabetic Malay women [Hubungan antara sensori neuropati dan ketidakseimbangan badan di kalangan wanita Melayu diabetik] - Kamaralzaman S.; Budin S.B.; Yau M.; Sidi H.; Sani A.; Mohamed J. (2024)
Indexed by SCOPUS